Urinary Metabolomics Study of Nucleosides in Rats Following Intraperitoneal Injection of γ-Hydroxybutyric Acid - Ji, Moongi; Park, Jiyeon; Choi, Byeongchan; Lee, Hyeon-Seong; Seo, Chan; Park, Meejung; Lee, Sooyeun; Paik, Man-Jeong (Marcel Dekker Inc., 2026)
γ-Hydroxybutyric acid (GHB) is a central nervous system depressant with high addiction risk, causing oxidative stress and neurotoxicity. Urinary nucleoside metabolomics studies in single- and multiple- administration rats have not been performed. Most nucleoside levels were higher in the single-administered group than the multiple-administered group. Multivariate analysis identified cytidine, pseudouridine, uridine, N4-acetylcysteine, adenosine, and 5’-deoxy-5’-methylthioadenosine as significant for group discrimination in principal component analysis (PCA) and partial least squares discriminant analysis (PLS-DA). These metabolites performed well in receiver operating characteristic (ROC) analysis, suggesting they could be potential biomarkers for GHB exposure and addiction.